2008
DOI: 10.1111/j.1462-2920.2008.01599.x
|View full text |Cite
|
Sign up to set email alerts
|

Disentangling the rhizosphere effect on nitrate reducers and denitrifiers: insight into the role of root exudates

Abstract: To determine to which extent root-derived carbon contributes to the effects of plants on nitrate reducers and denitrifiers, four solutions containing different proportions of sugar, organic acids and amino acids mimicking maize root exudates were added daily to soil microcosms at a concentration of 150 microg C g(-1) of soil. Water-amended soils were used as controls. After 1 month, the size and structure of the nitrate reducer and denitrifier communities were analysed using the narG and napA, and the nirK, ni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
196
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 262 publications
(213 citation statements)
references
References 67 publications
(85 reference statements)
14
196
2
Order By: Relevance
“…The lower concentration of nitrate might be because of the increased microbial activity observed in the rhizosphere, especially in contaminated soils, where bacteria were significantly more active and nitrate at its lowest concentration, being below the detection limit for two of the three replicates analyzed. Nitrate reduction was shown to be stimulated by root exudates (Henry et al, 2008), and, in this study, several nitrate reductase genes were more expressed in the rhizosphere of willow, offering another potential explanation for the lower nitrate concentration observed in the rhizosphere. Taken together, these data suggest that the stimulation of the rhizosphere hydrocarbon-degrading microorganisms by willows is not because of an increased nitrate input from the roots.…”
Section: Metatranscriptomics Of the Rhizospheresupporting
confidence: 49%
“…The lower concentration of nitrate might be because of the increased microbial activity observed in the rhizosphere, especially in contaminated soils, where bacteria were significantly more active and nitrate at its lowest concentration, being below the detection limit for two of the three replicates analyzed. Nitrate reduction was shown to be stimulated by root exudates (Henry et al, 2008), and, in this study, several nitrate reductase genes were more expressed in the rhizosphere of willow, offering another potential explanation for the lower nitrate concentration observed in the rhizosphere. Taken together, these data suggest that the stimulation of the rhizosphere hydrocarbon-degrading microorganisms by willows is not because of an increased nitrate input from the roots.…”
Section: Metatranscriptomics Of the Rhizospheresupporting
confidence: 49%
“…The addition of wheat residues had very limited effect on the denitrifier abundance monitored during 1 month. Accordingly, Miller et al (2008) showed that the number of the denitrifiers was not modified by the short-term addition of wheat, rape or alfafa residues and several studies suggest that carbon is not a strong driver of the denitrifier abundance in soil (Henry et al, 2008;Bru et al, 2011). Overall, serial dilution of the soil did not lead to a reduction in denitrifier abundances in the amended or non-amended microcosms after the pre-incubation period.…”
Section: Discussionmentioning
confidence: 87%
“…Similar nosZ clones have also been obtained from other paddy fields (for example, GenBank Accession No. ACI48848) and maize rhizospheric soils (Mounier et al, 2004;Dambreville et al, 2006;Henry et al, 2008). Considering the general agreement between the 16S rRNA gene and nosZ phylogenies (Jones et al, 2008;Palmer et al, 2009), these results suggested that Herbaspirillum and other Burkholderiales bacteria may be important players in N 2 O reduction, not only in rice paddy soils but also in other environments.…”
Section: Discussionmentioning
confidence: 99%